Analisis Penerapan Teori Legitimasi dalam Tanggung Jawab Sosial Perusahaan pada PT Kereta Api Indonesia Kiaracondong - Sari, Dewi Wulan; Gemellia, Livy Putrikita; Marlina, Neng; Kamilah, Al Manda Yasmin; Fathiya, Shifana Nurul (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2025)
This study aims to analyze the application of legitimacy strategy by PT Kereta Api Indonesia (KAI) through its Corporate Social Responsibility (CSR) program as part of responsible corporate governance practices. As a state-owned enterprise operating in the public transportation sector, PT KAI needs to maintain social legitimacy to sustain public trust and gain support from various stakeholders. This research adopts a qualitative approach using a case study method, focusing on PT KAI, and analyzing the documentation of its CSR programs. The findings show that PT KAI utilizes CSR programs not only to comply with regulatory requirements but also as a means to build a positive corporate image by addressing social issues such as infrastructure development, environmental conservation, and educational support. This strategy has proven effective in strengthening the company's social legitimacy, especially in meeting public expectations. Based on these findings, this study recommends strengthening the evaluation of CSR impact systematically to ensure the sustainability of social legitimacy.